A Teleneuropsychology Protocol for the Cognitive Assessment of Older Adults During COVID-19 - Kitaigorodsky, Marcela; Loewenstein, David; Curiel Cid, Rosie; Crocco, Elizabeth; Gorman, Katherine; González-Jiménez, Christian (Frontiers in Psychology, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic prompted the need for a teleneuropsychology protocol for the cognitive assessment of older adults, who are at increased risk for both COVID-19 and dementia. Prior recommendations for teleneuropsychological assessment did not consider many of the unique challenges posed by COVID-19. The field is still in need of clear guidelines and standards of care for the assessment of older adults under the current circumstances. Advantages of teleneuropsychological assessment during the COVID-19 pandemic include reduced risk of contracting the virus, eliminating travel time and reducing cost, and more rapid access to needed services. Challenges include disparities in technology access among patients, reduced control over the testing environment, impeded ability to make behavioral observations, and limited research on valid and reliable cognitive assessment measures. The aim of this perspective review is to propose a teleneuropsychological protocol to facilitate neuropsychological assessment utilizing a virtual platform. The proposed protocol has been successful with our clinical and research populations and may help neuropsychologists implement teleneuropsychology services without compromising validity or reliability. However, there is increasing need for research on teleneuropsychological assessment options for both clinical and research purposes.